The Differences of TNF-Î± Levels and BMI in Diabetic Patients with Pulmonary Tuberculosis After Intensive Phase of Tuberculosis Treatment - Lydia, Wika; Nasution, Melati Silvanni; lubis, Dian Anindita; Muhammad Aron Pase (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Abstract. Introduction. Diabetes Melitus (DM) can cause complications, such as pulmonary tuberculosis (TB). Metabolic disorders are thought to be related to Tumor Necrosis Factor-Î± (TNF-Î±) metabolism, adipocytokines secreted by macrophages, which inhibit insulin transduction, has anti-mycobacterial activity, however, also negatively affect pathological TB process. This study aims to determine differences in TNF-Î± levels and Body Mass Index (BMI) in DM with pulmonary TB after intensive phase of antituberculosis treatment. Method. This prospective comparative analytical study with one-group pretest-posttest design, conducted during August 2019-September 2019 in outpatient of Type 2 DM with pulmonary TB at USU Hospital, Madani Medan Hospital, Teladan Health Center and Laboratory of Haji Adam Malik Medan after approval from the Health Research Ethics Commission. Data were analyzed after normality test, then mean difference and correlation test by using the SPPS program where p <0.05 was considered significant. Results. This study showed an increase BMI, and decrease of fasting blood glucose, 2-hour post-prandial blood glucose, HbA1C and TNFÎ± levels before and after intensive phase of antituberculosis treatment (p = 0,000; p = 0,000; p = 0,000; p = 0,000). Conclusion. There was a significant increase of BMI and decrease of TNFÎ± level after intensive phase of antituberculosis treatment.